Pengaruh Profesionalisme Kerja Terhadap Kualitas Pelayanan Publik pada Kantor Kecamatan Gunungsindur - Selsya Billa Regita; Izzatusholekha Izzatusholekha (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
In this study, one of the problems is the lack of understanding of employees in carrying out their duties, this is due to the lack of training and competency development, periodic evaluations, and lack of supervision from leaders, resulting in ineffectiveness in public services provided to the community. This study aims to determine the effect of work Professionalism On The Quality Of Public Services In Gunungsindur District Office. This study uses the theory of factors that support work professionalism (Kurniawan:2005), namely Apparatus Ability, Experience, Loyalty, Performance, Punctuality. And the theory of public service quality categories (Parasuraman:2011) namely Tangible, Reliability, Responsiveness, Assurance, Empathy. The method used in this study is a quantitative method with an associative research type. Data collection techniques in this study with observation, documentation, and questionnaires. This study uses a sampling technique using purposive sampling with a total of 99 respondents. The data analysis techniques used are validity test, reliability test, normality test, simple linear regression analysis, determination coefficient, correlation coefficient, hypothesis test (t test). The results of this study explain that there is an Influence of Work Professionalism on the Quality of Public Services in Gunungsindur District Office, this is obtained from the results of the hypothesis test which has a t count value of 9,161 which is greater than the t table value of 1.660 and has a significant level of 0.000 less than 0.05.